Routing packets to distant locations in VANETs - Mershad, Khaleel (2011)
In the near future vehicular networks (VANETs) based on wireless technology will be part of our daily lives. VANETs enable vehicles that are not necessarily within the same transmission range to communicate with each other. They also allow vehicles to connect to Roadside Units (RSUs), which are connected to the Internet, forming a backbone mesh that offers the capability of communicating with each other and with roaming vehicles. In this paper, we exploit the RSU network to efficiently route packets between far away vehicles in the VANET. We evaluate our system using ns2 simulation, and compare it to existing solutions. The results demonstrate the feasibility and efficiency of our proposed scheme in terms of query delay, packet delivery ratio, and generated traffic.